The Influence of Information Access, Knowledge, Perception of Family Planning’s Risks, and Husband’s Support on Interest of Using Contraception for Unmet Need Group - Yuliati, Lilik Noor; Simanjuntak, Megawati; Oktriyanto, Oktriyanto (Jurnal Ilmu Keluarga dan Konsumen, 2019)
This study aims are to analyze the influence of information access, knowledge, perception of contraception for birth control risk, and husband's support on unmet need group’s interest in using contraception. This research used a cross-sectional study design and survey method. The research was conducted in Bogor City, Indonesia with 200 respondents (wives). Data was collected through face-to-face interview. Data were analyzed descriptively and inferred using Structural Equation Modelling (SEM). The respondents were selected purposively. Based on research’s result, the wife’s knowledge regarding contraception using was in the medium category. However, knowledge about contraception devices was still in the low category. In this research, wives perceive that family planning has little risk for health and non-health. Husband’s support was categorized as good and the husbands allowed their wife to use contraception but did not get involved in the decision-making. The respondents had reasonably good interest in contraception using by considering 6 to 10 respondents prefer not to use contraception. Research result showed the accepted hypothesis are access to information influences knowledge (H1), perceived risk influences interest (H5), access to information does not influences risk perception (H2), knowledge does not influence risk perception (H3), knowledge has no effect on interest (H4), so does husband's support (H6).